2013
DOI: 10.1007/s12272-013-0248-6
|View full text |Cite
|
Sign up to set email alerts
|

BF-30 effectively inhibits ciprofloxacin-resistant bacteria in vitro and in a rat model of vaginosis

Abstract: Bacterial infections are becoming increasingly difficult to treat due to the increasing number of multidrug-resistant strains. Cathelicidin-BF (BF-30) is a cathelicidin-like antimicrobial peptide and exhibits broad antimicrobial activity against bacteria. In the present study, the antibacterial activity of BF-30 against ciprofloxacin-resistant Escherichia coli and Staphylococcus aureus was examined, and the protective effects of this peptide against these bacteria in rats with bacterial vaginosis were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Cathelicidin-BF (C-BF or BF-30) was derived from the snake venoms of the Chinese endemic genera Bungarus fascia and is considered to be a potent peptide antibiotic [18]. Cathelicidin-BF displayed effective antimicrobial activities against ciprofloxacin-resistant Escherichia coli and Staphylococcus aureus [19]. In addition, C-BF displayed higher antibacterial activity against enteric pathogens isolated from the feces of diarrheal weaned piglets than other cathelicidin peptides [12].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Cathelicidin-BF (C-BF or BF-30) was derived from the snake venoms of the Chinese endemic genera Bungarus fascia and is considered to be a potent peptide antibiotic [18]. Cathelicidin-BF displayed effective antimicrobial activities against ciprofloxacin-resistant Escherichia coli and Staphylococcus aureus [19]. In addition, C-BF displayed higher antibacterial activity against enteric pathogens isolated from the feces of diarrheal weaned piglets than other cathelicidin peptides [12].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…Oestrogen combined with E. coli is a widely used method to establish animal models of BV. Along with the high stability, these models can simulate the pathogenesis and clinical manifestation of BV (Wang et al , b). In the present study, this animal model was successfully established and confirmed by detecting the symptom indexes, CFU and neutrophil count, providing a solid guarantee for the subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…These peptides are broad-spectrum antimicrobial peptides that are active against clinical and standard strains of bacteria and pathogenic fungi, including antibiotic-resistant isolates (Wang et al 2008(Wang et al , 2013cZhao et al 2008;Falcao et al 2014;Xia et al 2015). Interestingly, in a study using a mouse model of endotoxemia as induced by an intraperitoneal injection of lipopolysaccharide, Bungarus fasciatus cathelicidin precluded the damage and the cell death that were provoked by LPS to the intestinal epithelium.…”
Section: Vipericidins and Snake Venom Cathelicidin-related Peptidesmentioning
confidence: 99%
“…Advanced research about the multiple actions of snake cathelicidins has revealed that apart from displaying an efficacious killing effect against microbes, elapid CRAMPs (Tian et al 2013;Wang et al 2013c) and vipericidins (unpublished personal data) are cytotoxic for different types of tumor cells. The mechanisms by which snake venom cathelicidin kills bacterial and tumor cells are also conserved.…”
Section: Vipericidins and Snake Venom Cathelicidin-related Peptidesmentioning
confidence: 99%